Arsenic in central Massachusetts bedrock and groundwater - McTigue, David F.; Stein, Carol L.; Brandon, William C.; Joseph P Kopera; Keskula, Anna J.; Koteas, G. Christopher (Abstracts with Programs - Geological Society of America, 2010)
Across the New England "arsenic belt," groundwater arsenic (As) concentrations often exceed the EPA's 0.01-mg/L drinking water standard. In overburden groundwater at a site within this belt in north-central Massachusetts, As has been reported at levels up to 7.6 mg/L. Bedrock at the site consists of Silurian Central Maine Terrane metasediments intruded by the Devonian Ayer granodiorite and Chelmsford granite. Exchange of hydrothermal fluids between these lithologies during intrusion and later deformation, faulting, and metamorphism resulted in crystallization of arsenic-bearing minerals, including arsenopyrite. Quaternary deglaciation and unloading dilated joint systems in the bedrock, allowing increased exposure of the mineralogy to meteoric water. Several arsenopyrite alteration products (e.g., scorodite), of varying solubilities, precipitated on fracture surfaces and along grain boundaries between major phases. In the emerging conceptual model for this site, groundwater is recharged in bedrock uplands and moves downgradient through the fracture network, becoming increasingly reducing as it moves along a flow path. Arsenic dissolved from arsenopyrite and arsenic-bearing alteration phases in bedrock remains in solution until the groundwater discharges to lowland areas hydraulically downgradient. In these adjacent lowlands, glacial sand and gravel overburden lies above the bedrock. When the reducing water reaches more oxidizing conditions, As-sorbing hydrous ferric oxides (HFO) precipitate out on the aquifer solids, resulting in accumulation of As in the deep overburden aquifer. A large landfill at this site, now closed and capped, imposed reducing conditions, and As is mobilized into groundwater by reductive dissolution of the HFO. The presence of elevated As in groundwater is consistent with arsenic-bearing phases generated in granitoids at depth during regional metamorphism, which were subsequently altered, and are being solubilized at present by the circulation of shallow groundwater through varying redox environments. This scenario is supported by geochemical and petrographic studies of the granitoids and the occurrence of the highest groundwater and soil arsenic concentrations in the adjacent deep overburden.
Keywords: #StaffPubs; alteration; arsenic; arsenides; arsenopyrite; Ayer Granodiorite; BEDROCK; central Massachusetts; chelmsford granite; Devonian; dilation; discharge; dissolved materials; drinking water; Eh; fractures; General geochemistry 02A; geochemistry; granites; ground water; igneous rocks; joints; massachusetts; metals; metamorphism; meteoric water; overburden; Paleozoic; petrography; plutonic rocks; pollutants; reduction; solubility; solution; sulfides; theoretical models; United States

Deep geothermal potential of New England granitoids; the Fall River Pluton, southeastern Massachusetts - Goodhue, Nathaniel; Koteas, G. Christopher; John Michael Rhodes; Stephen B Mabee (Abstracts with Programs - Geological Society of America, 2011)
Devonian-aged plutonic rocks that are interpreted to be part of the Fall River pluton, along the southern edge of the Narragansett Basin, appear to have potential as a source of deep geothermal energy. The Narragansett Basin covers a approximately 1500 Km (super 2) area in southern Massachusetts and is dominated by complexly deformed and metamorphosed, Pennsylvanian-aged, fluvial and alluvial deposits. A northeast-striking series of brittle faults and discrete shear zones define the southern margin of the basin. Preliminary modeling of igneous and gneissic fabrics from outcrops along the southern edge of the basin show that the granite dips predominantly north, northeast. This pattern suggests that granitoids along the southern edge of the basin continue beneath the Narragansett Basin and correlate with granitoids exposed to the north. Regional joint sets in the Fall River pluton can be grouped into three dominant clusters at 350 degrees , 90 degrees , and 250 degrees based upon 86 field measurements. Low-angle sheeting joints are also common and suggest interconnected fracture networks at depth. Preliminary geochemistry from the Fall River pluton suggests that feldspars and accessory minerals contain the appropriate concentrations of heat producing elements, primarily U, Th, and K, to be a reasonable geothermal resource. K (sub 2) O values range from 2.4 to 5.0 weight percent. U and Th values (in ppm) range from 0.9 to 6.2 and 2.9 to 30.1 respectively. Assuming a relatively consistent composition at depth, a density of 2.6 kg/m (super 3) , and a thermal conductivity of 2.9 W/m degrees C, initial temperature modeling suggests average temperatures of 81 degrees C at depths of 5 kilometers and 93 degrees C at depths of 6 kilometers. Temperature estimates increase to approximately 150 degrees C and approximately 170 degrees C respectively when a two kilometer thick sediment package is modeled overlying the granitoids. The goal of current and future work is to improve assumptions about compositional uniformity as well as the regional position of granitoids at depth. At the conclusion of this work we hope to develop a protocol for studying geothermal potential of buried granitoids in New England in the absence of reliable drill-hole data. Preliminary estimates from this project suggest that basins underlain by granitoids of compositions similar to that of the Fall River pluton have reasonable potential as a deep geothermal resource.
Keywords: #StaffPubs; depth; Economic geology, geology of energy sources 29A; Fall River Pluton; geochemistry; geothermal energy; gneisses; granites; Igneous and metamorphic petrology 05A; igneous rocks; intrusions; massachusetts; metamorphic rocks; plutonic rocks; plutons; southeastern Massachusetts; United States

Evidence for arsenic-mineralization in granitic basement rocks, Ayer Granodiorite, northeastern Massachusetts - Koteas, G. Christopher; Keskula, Anna J.; Stein, Carol L.; McTigue, David F.; Joseph P Kopera; Brandon, William C. (Abstracts with Programs - Geological Society of America, 2010)
Core samples of the Ayer Granodiorite along the eastern margin of the Merrimack Belt in northeastern Massachusetts host a series of sulfide and oxide phases that resulted from interaction with sulfide-bearing meta-sedimentary host rocks. Euhedral arsenopyrite grains are found with ilmenite, apatite, and REE phosphates in zones that generally mimic the intersection between a gneissic fabric and a relict magmatic foliation. Arsenopyrite crystals are typically elongate with this lineation. Euhedral to subhedral pyrite crystals have also been observed, but are localized to areas without As-bearing phases. Micro-fractures that parallel either a steep NW-striking joint set or gently-dipping sheeting joints are commonly filled with interwoven calcite cements and As-bearing Fe-oxides. Surface coatings of major fracture sets are also characterized by Fe-As-rich rinds that host micron-scale sub-angular particles of quartz, feldspars, and phyllosilicates. Where micro-fractures are most concentrated, sulfide-bearing minerals are less common; however, subhedral to anhedral arsenopyrite grains do occur along some open micro-fractures. These crystals preserve lobate grain boundaries and are associated with As-bearing Fe-oxide-rich coatings along adjacent fractures. The presence of 1) pyrite, 2) arsenopyrite associated with phosphates, and 3) As-bearing fracture coatings suggests multiple stages of mineralization. We propose that intrusion-related fluid-rock interaction associated with heating of nearby sulfide-bearing schists of the Berwick Formation during Acadian orogenesis may have provided the necessary constituents for growth of sulfide phases in the Ayer. It appears that Late Devonian greenschist facies metamorphism and metasomatism led to mineralization that generated arsenopyrite and accompanying phosphates; however, the role of the cross-cutting Clinton Newbury Fault Zone as a conduit for hydrothermal fluids may also be important. Lower temperature As-bearing Fe-oxide and calcite coatings on open fractures surfaces may be associated with a change from lithostatic- to hydrostatic-pressures during post-glacial regional uplift. This mineralization appears to be synchronous with intense microfracturing that post-dates all other mineralization.
Keywords: #StaffPubs; acadian; arsenic; arsenides; arsenopyrite; Ayer Granodiorite; Berwick formation; fractured materials; geochemistry; granodiorites; Igneous and metamorphic petrology 05A; igneous rocks; lower Paleozoic; massachusetts; Merrimack Synclinorium; metals; metamorphic rocks; metamorphism; metasedimentary rocks; metasomatism; Middlesex County Massachusetts; migration of elements; mineralization; Mineralogy of non-silicates 01C; northeastern Massachusetts; orogeny; Paleozoic; plutonic rocks; pollutants; pollution; pyrite; sulfides; United States

Identifying and examining potential geothermal resources in non-traditional regions, examples from the northeastern U.S. - Koteas, G. Christopher; John Michael Rhodes; Stephen B Mabee; Goodhue, Nathaniel; Adams, Sharon A. (Abstracts with Programs - Geological Society of America, 2011)
The search for geothermal resources is rapidly expanding into tectonic regions that have not been previously considered to be suitable for exploitation. Many of these regions, such as the northeastern U.S., have never been the site of extensive geophysical investigations and have few deep borehole temperature measurements. Nevertheless, large portions of the northeastern U.S. are underlain by granitic bedrock that may be a productive energy source by applying enhanced geothermal technologies. In the absence of traditional reconnaissance data, we utilize field studies and sampling together with geochemical analysis to develop models of geothermal resources that can be tested against data from deep boreholes. Heat production is calculated from the measured density of the samples, the concentrations of K, U, and Th from whole-rock geochemical analysis via X-ray fluorescence, and established radiogenic heat production values. Models for a particular area can then be generated by calculating depth-specific temperatures using heat production, measured thermal conductivity for each sample, and assumptions related to local stratigraphy and regional heat flow. Mapping and structural extrapolation are used to establish the subsurface characteristics at a study site and are combined with the thermal and chemical characteristics of contact rocks and overburden materials. Two examples of the application of this technique are the Fall River granite at the margin of the Narragansett Basin in southeastern Massachusetts and the Andover Granite in northeastern Massachusetts. Thermal models of the Fall River Pluton indicate average temperatures of 71 degrees C at depths of 4 km and 97 degrees C at 6 km. Average temperatures increase to 107 degrees C and 132 degrees C, respectively, when a 2 km thick sediment package is modeled overlying the granite. The Andover Granite, which is not associated with a sedimentary basin and is in a more structurally complex configuration, yields an average temperature of 74 degrees C at a depth of 4 km and 101 degrees C at 6 km. While this approach to modeling temperature-depth profiles requires some regional heat flow assumptions, the application of mapping and structural analysis with geochemistry and thermal conductivity studies can be an important reconnaissance tool for identifying non-traditional geothermal resources.
Keywords: #StaffPubs; Andover Granite; Eastern U.S.; Economic geology, geology of energy sources 29A; exploitation; exploration; Fall River Granite; field studies; geochemistry; geothermal energy; identification; mapping; massachusetts; models; Northeastern U.S.; overburden; resources; sampling; southeastern Massachusetts; spectra; structural analysis; technology; temperature; United States; whole rock; X-ray fluorescence spectra

Implications for non-traditional geothermal resources in southern New England; variability in heat potential based on thermal conductivity and geochemistry studies - Koteas, G. Christopher; John Michael Rhodes; Stephen B Mabee; Ryan, Amy; Schmidt, Joe; League, Corey; Goodhue, Nathaniel; Adams, Sharon A.; Gagnon, Teresa K.; Thomas, Margaret A. (Abstracts with Programs - Geological Society of America, 2012)
Estimating geothermal potential in southern New England in the absence of borehole heat flow data or geophysical studies has led to a focus on models based on thermal conductivity, geochemistry, and density-based heat production models. Preliminary estimates of geothermal potential generally match borehole-based heat flow data from similar tectonic environments. Nevertheless, microstructural and compositional heterogeneity with depth remain largely unconstrained. The extrapolation of regional structures based on detailed field mapping has helped to improve structural projections adjacent to major basins. However, an additional source of error in models of heat potential-with-depth are thermal conductivity estimates of igneous and meta-igneous rocks throughout Massachusetts (MA) and Connecticut (CT). Over three hundred granitoid localities in MA and CT have been analyzed to date. The southern New England region can be simplified into four major litho-tectonic zones: the Taconic-Berkshire Zone of western MA and northwestern CT, The Bronson Hill Zone associated with the CT River valley, the Nashoba Zone of central MA and eastern CT, and the Milford-Dedham Zone of eastern MA and eastern CT. Granitic rocks adjacent to the CT River valley and the Narragansett Basin vary considerably in thermal conductivity. Granites adjacent to the Narragansett Basin vary from 2.9 to 3.7 W/m * K. Average thermal conductivity values, combined with modeled heat production values, produce temperatures at 3 km depth along the Narragansett Basin that approach 85-115 degrees C. Values of meta-igneous rocks from the margin of the CT River valley in MA and CT vary more considerably in thermal conductivity, from 1.8 to 3.9W/m * K. Modeled heat potentials at 3 km depths along the eastern margin of the CT River valley vary between 74-122 degrees C and appear to be largely related to compositional variation. However, local rock composition is also related to metamorphic grade and fabric development, suggesting that both fabric and composition are first order controls on thermal conductivity. Modeling based on these data set to date suggests that combining thermal conductivity, whole rock geochemistry data, and density measurements can produce accurate reconnaissance estimates of geothermal potential in southern New England.
Keywords: #StaffPubs; chemical composition; Connecticut; Economic geology, geology of energy sources 29A; energy sources; geothermal energy; geothermal exploration; granites; heat flow; igneous rocks; massachusetts; models; New England; plutonic rocks; thermal conductivity; United States